Memorization in DSS, NT, Talmud and Patristic Documents - Philip Suciadi Chia; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
The history of civilization has its own uniqueness. There is an era in which all forms of knowledge must be memorized. However, after the advent of the printing press, many books circulated that could be a source of knowledge. And after this post-modern era arrives, all knowledge is available at hand via smart-phone at any time.According to historical records, education in the Jewish tradition is very strict. From an early age, a human child has been accustomed to remember what has been learned as part of life. There are four records in history to understand the practice of learning in understanding God's Law carefully and memorizing it. These sources from different eras testify simultaneously that memorization is a must for Jewish education context both at home, public school and synagogue. The sectarian, in Qumran, maintained their own strict interpretation of the Law. Family was still the chief institution and primary context for the dispensation of elementary instruction; although the scribes, Pharisees and learned rabbis played a major role in Jewish education during the NT era. Talmud is more specific about the age of studying and the sign of mastering. Origen also was trained since his childhood by his father, Leonides, to memorize Scripture daily and recite them every day.